Análisis administrativo del patronato municipal del niño de Quevedo (PAMUNIQ) y su incidencia en la calidad de servicio, año 2013 - Hermosa saltos, Milton Enrique (2013)
In the present research focused on finding the main problems related to the quality of service provided by the Municipal Child Quevedo, in the course of the investigation, it became apparent observe the service provided to the user as well as the different procedures have to make their users in the organization, as well as its infrastructure, it does not supply the same demand of users. The research results are supported by surveys and discussions with the administrative staff as well as users who attend the service, the study was based on inductive methods, descriptive, the first thing was to talk to the coordinator and Pamuniq as well as with the administrative staff, which allowed to hear cases on issues relevant organization with quality service. In the theoretical framework are vital aspects, these being in different theories which correspond to the appearance authors studied, in terms of sustaining remarkably Management Analysis research, this is important for the development of diagnostic respective allowing readers to document arguments clear about the administration of the Municipal Quevedo canton child, in order to recommend mechanisms for solving the problems encountered. The research population of a total of 3,200 users, a sample was taken, to 401 people, including administrative staff as well as the people who come to Pamuniq in search of their preferred service in Canton Quevedo, was performed with the provisions a situational analysis of the various problems in the departments of the organization, particularly in areas related to human talent and quality of service. In the end, after the survey was a starting point in this research confirmed the need to improve service quality, it served as a tool for statistical analysis and interpretation of data to reach conclusions and recommendations that will help improve the quality of service for users of the Municipal Quevedo Canton toddler.